Avoiding errors in paediatrics - Raine, Joseph E. (AVE - Avoiding Errors., 2013)
Identifies and explains the most common errors likely to occur in a pediatric setting. Discusses causes of errors, complaints and medico-legal consequences, and offers case scenarios, expert and legal comment, and clinical teaching points and strategies to help the reader engage in safer practice throughout a career in pediatrics.